2009
DOI: 10.1007/s10165-009-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

A new low-field extremity magnetic resonance imaging and proposed compact MRI score: evaluation of anti-tumor necrosis factor biologics on rheumatoid arthritis

Abstract: Magnetic resonance imaging (MRI) is a useful tool for evaluating disease activity and therapeutic efficacy in rheumatoid arthritis (RA). However, conventional whole-body MRI is inconvenient on several levels. We have therefore developed a new low-field extremity MRI (compact MRI, cMRI) and examined its clinical utility. Thirteen RA patients treated with anti-tumor necrosis factor (TNF) biologics were included in the study. The MRI was performed twice using a 0.21-T extremity MRI system. The MRI images were sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Significant advances have been made within the field of imaging in rheumatic diseases over the past decade [3]. Magnetic resonance imaging is a useful tool for evaluating disease activity and therapeutic efficacy in rheumatoid arthritis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Significant advances have been made within the field of imaging in rheumatic diseases over the past decade [3]. Magnetic resonance imaging is a useful tool for evaluating disease activity and therapeutic efficacy in rheumatoid arthritis [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of disease activity in RA patients within 1 year of beginning treatment with the anti-IL 6 receptor antibody tocilizumab, MR bone erosion is both responsive and predictive of structural damage progression at 1 year. The second point that deserves discussion: that is the low field MRI is also reliable and useful than the high field Low field dedicated E-MRI units have previously, been shown to allow detection of inflammatory and destructive joint damage in RA, moreover, E-MRI have shown the ability to detect the development of structural joint damage [6,18,32,33]. E-MRI is favored by low costs and also because patient positioning is more comfortable and claustrophobia is avoided and can be easily used for follow-up of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary studies confirmed the efficacy of this novel MRI system for the early diagnosis of RA and for precise imaging of joint destruction in advanced-stage RA patients. We also showed that this machine is useful for evaluating the effects of biological agents [6]. Our proposed compact MRI score has also simplified the assessment of RA activity [6].…”
Section: Introductionmentioning
confidence: 98%
“…We also showed that this machine is useful for evaluating the effects of biological agents [6]. Our proposed compact MRI score has also simplified the assessment of RA activity [6].…”
Section: Introductionmentioning
confidence: 98%